Interlayer vibrational modes in few-quintuple-layer Bi2Te3 and Bi2Se3 two-dimensional crystals: Raman spectroscopy and first-principles studies - Zhao, Yanyuan (American Physical Society, 2020)
10.1103/PhysRevB.90.245428